Nanotheranostics With the Combination of Improved Targeting, Therapeutic Effects, and Molecular Imaging - Peng, Shin-Lei; Lai, Chih-Ho; Chu, Pei-Yi; Hsieh, Jer-Tsong; Tseng, Yen-Chun; Chiu, Shao-Chieh; Lin, Yu-Hsin (Frontiers in Bioengineering and Biotechnology, 2020)
There are increasing interest to design targeting carrier systems with combined therapeutic and diagnostic modalities. Therapeutic targeting tumors single ligand-based targeting nanocarriers are insufficient for proficient delivery and for targeting two different surface receptors overexpressed in cancer cells. Here we evaluated an activated nanoparticle delivery system comprising fucoidan/hyaluronic acid to improve therapeutic efficacy. The system comprised polyethylene glycol-gelatin-encapsulated epigallocatechin gallate, poly (D,L-lactide-co-glycolide), and stable iron oxide nanoparticles. The latter enables targeting prostate cancers in the molecular images. We show the transfer of nanoparticles and their entry into prostate cancer cells through ligand-specific recognition. This system may prove the beneficial of drug delivery that enhance the inhibition of cell growth through inducing apoptosis. Moreover, the improved targeting of nanotheranostics significantly suppressed orthotopic prostate tumor growth and more accurately targeted tumors compared with systemic combination therapy. With the present of nanoparticle with iron oxides, the hypointensity of prostate tumor was visualized in the T2-weignted magnetic resonance image. The diagnostic ability of this system was demonstrated by accumulating fluorescent nanoparticles in the prostate tumor from the in vivo imaging system-computed tomography. It is suggested that the theranostic nanoparticles combined with molecular imaging system can be a promising cancer therapy in the future.